Association of pituitary neuroendocrine tumors and neurofibromatosis type 1: assessing causation versus coincidence. Case report - Aguilar-Soto, Mercedes; Zuarth-Vázquez, Julia M.; Leyva-Figueroa, Laura; Zarco-Ávila, Karla; Gamboa-Domínguez, Armando; Eguiluz-Melendez, Aldo; Hernández-Ramírez, Laura C. (Frontiers in Endocrinology, 2025)
IntroductionPatients with neurofibromatosis type 1 (NF1) are at risk for developing various neoplasms. Since the early twentieth century, multiple cases of pituitary neuroendocrine tumors (PitNETs) occurring in this context have been published. Yet, the role of NF1 (17q11.2) loss-of-function (LOF) variants in pituitary tumorigenesis remains unclear.AimWe report the clinical and molecular characterization of a case of PitNET diagnosed in a patient with NF1. We also review the available data for and against a causal association between NF1 defects and pituitary tumors.MethodsOur patient was recruited via an ongoing prospective study of individuals with neuroendocrine neoplasms. Genetic testing was carried out by means of targeted next generation sequencing (NGS) and Sanger sequencing in blood and tumor DNA, respectively. NF1 expression was analyzed via quantitative polymerase chain reaction (qPCR) in blood and tumor cDNA. Similar cases were searched in the literature.ResultsA 54-year-old-man was incidentally diagnosed with a clinically non-functioning PitNET via brain imaging. He had a personal and family history of NF1 and carried the germline pathogenic variant NF1 (NM_001042492.3): c.147C>A, p.Y49*. Via transsphenoidal surgery, a 16 mm lesion was resected, showing strong granular cytoplasmic immunoreactivity with patchy distribution for NF1 and preserved heterozygosity for the NF1 defect. Additional NGS ruled out germline defects in PitNET-associated genes. By qPCR, NF1 was significantly overexpressed in the tumor when compared with another NF-PitNET, but not when compared with a corticotropinoma. We reviewed twenty-three case reports of PitNETs occurring in patients with either clinical NF1 without genetic study, individuals with NF1 germline variants with or without clinical NF1 or associated with somatic NF1 defects. Predominance of GH-secreting and large PitNETs, with young-onset in around half of the cases, were noticed. Two individuals developed multiple endocrine neoplasia-like phenotypes but tested negative for other relevant genetic defects.ConclusionsAlthough the association of NF1 and PitNETs could be coincidental, the clinical characteristics of the reviewed cases differ from those of typical incidentalomas. NF1 could drive pituitary tumorigenesis via haploinsufficiency, but this hypothesis requires further research. Additional clinical and molecular data from large cohorts of affected individuals should help clarify this question.